Self-healing graphene-based composites with sensing capabilities - D'Elia,E; Barg,S; Ni,N; Rocha,VG; Saiz,E (Advanced Materials, 2015)
A self-healing composite is fabricated by confining a supramolecular polymer in a graphene network. The network provides electrical conductivity. Upon damage, the polymer is released and flows to reform the material. Healing is repeatable and autonomous. The composite is sensitive to pressure and flexion and recovers its mechanical and electrical properties even when rejoining cut surfaces after long exposure times.